Between the taiga and the steppe: a new find of the “bears in a sacrificial pose” plaque from the Upper Ob region - Fribus A.V.; Grushin S.P. (Вестник археологии, антропологии и этнографии)
The purpose of this study is a comprehensive analysis of a new find of a plaque depicting “bears in a sacrificial pose” from the Chumysh-Perekat necropolis. Such artifacts were widespread in the early Middle Ages in the taiga, forest and forest-steppe zone of Eurasia in vast territories from the Urals to the Achinsk-Mariinsk forest-steppe. The Chumysh-Perekat necropolis is located in the Upper Ob region, in the north-east of Altai Krai, on the right bank of the River Chumysh. Seventeen early medieval burials of the Odintsovo Culture have been studied there. The plaque was found in women's grave No. 30. The grave goods included some decorations and fragments of belt sets, which have similarities in complexes of the Kudyrge stage. At the same time, the plaque depicting “bears in a sacrificial pose” only finds analogies in the north, in necropolises of the Novosibirsk and Tomsk Ob regions. To date, more than 100 rectangular plaques with images of “bears in a sacrificial pose” are known. The presented find is one of the southernmost in Western Siberia. This artifact belongs to the vertical class, group 3 (depicting three bear heads), type 2 (the plate is divided into three vertical stripes, the bear heads are positioned on the central, widest part), subtype 3 (with a detailed imaging of bears’ face and paws), according to the typology of Yu.P. Chemyakin. Metal analyses show that the compositions of alloys used for the production of the plaques and belt sets found on site differ significantly. A copper-silver-tin-zinc alloy and lead brass were used for manufacturing belt plates. The plaque with “bears in a sacrificial pose” is made of copper-lead-tin alloy. The complex has been dated to the middle of the 7th — turn of the 8th c. AD. The micro-collective, whose representatives were buried in the Chumysh-Perekat, apparently was of a high social status. This is indicated by several facts: the presence of a number of male burials with a horse, the presence of “rich” and extraordinary female graves which include decorations, both of local origin and characteristic of the “Turkic” and “Ugric” world, finds of belt sets not only in male, but also in female and children’s burials, etc.